Investigation of some hematological parameters in the hamdani sheep - Ayşegül Bildik; Fatmagül Yur; Ferda Belge; Yeter Değer; Semiha Dede (Eurasian Journal of Veterinary Sciences)
In this study, 15 Hamdani sheep and 4 rams belong to Research Center o( University of Yüzüncü Yıl were used as research material. Using spectrophoiometric tecnique the whole blood sample and plasma were analysed for the determination of the levels of glutathione, ceruloplasmin, Cu, Ca and P. In addition, haematocrit was determinated by using microhaematocrit technique. Animals having over 25 mg/dl glutathione were designated as high glutathione type (GSHH). Values of GSHH. GSHh, ceruloplasmin, Cu, Ca, P and haematocrit in Hamdani sheep were 30.8 ± 1.7 mg/dl, 11.88 ± 2.2 mg/dl, 12.68 ± 0.87 mg/dl, 75 ±23 (g/dl. 6.71 ± 0.4 mg/dl, 14.74 ± 0.63 mg/dl, % 33 ±0.37, respectively. These values in Hamdani rams also were 32.8 mg/dl, 22 ± 0.25 mg/dl, 12 ± 2.9 mg/dl, 91±40 (g/µdl, 9,45 ± 2.1 mg/dl, 5.69 ± 1.7 mg/dl and % 36.7 ± 1.3, respectively. Statisticaly positive correlation was found between Cu and ceruloplasmin concentration of plasma (p<0.05).